Testing if Micro-CT Is Capable of Quantitating the Extent of Proteoglycan-Aggrecan Induced Axial Spondyloarthritis in Mice - Han, Qing; Zheng, ZhaoHui; Liang, Qiang; Zhang, Kui; Yang, FengFan; Fu, XiangHui; Luo, Xing; Ding, Jin; Xie, Ronghua; Zhu, WenXiao; Zhu, Ping (Frontiers in Immunology, 2021)
Objective: Injections of proteoglycan aggrecan (PGA) have been reported to induce axial spondyloarthritis (ax-SpA) in BALB/c mice. It is considered to be a model for radiographic ax-SpA. However, evaluation of the extent of axial disease by histopathological assessment of every intervertebral space is labor-intensive. The objective of our paper is to test the feasibility of Micro Computed Tomography (Micro-CT) in rapidly enumerating the number of intervertebral spaces affected in each mouse. Methods: Arthritis was induced in BALB/c mice by intraperitoneal injections of PGA. Involvement of several spinal segments, and selected sacroiliac and hip joints were evaluated by histopathology. The involvement of all intervertebral spaces, sacroiliac and hip joints was evaluated by Micro-CT. Results: BALB/c mice injected with PGA developed histopathology of SpA-like axial lesions, including spondylitis, sacroiliac joint arthritis and hip joint arthritis. Micro-CT allowed us to clearly enumerate the number of lesions in each mouse. Conclusion: Micro-CT allows quantitative assessment of the extent of axial involvement in PGA-induced mouse spondylitis. This can be a useful tool in assessing therapeutic interventions.